Complete mitochondrial genome of "Xenopus tropicalis" Asashima line (Anura: Pipidae), a possible undescribed species. (2nd September 2016) - Haramoto, Yoshikazu; Oshima, Tomomi; Takahashi, Shuji; Asashima, Makoto; Ito, Yuzuru; Kurabayashi, Atsushi
Abstract: The diploid Xenopus tropicalis, with its small nuclear genomic size and short generation time compared to the traditional experimental amphibian X. laevis, is considered a next-generation model animal. Several experimental X. tropicalis lines have been used in research studies. Previous studies showed that the mtDNA sequence of the Asashima line is divergent from other lines and that this line may represent a distinct species. Here, we report the complete nucleotide sequence of this unique X. tropicalis experimental line . The genome is 17, 700 bp in length and contains 37 genes commonly found in animal mtDNAs. The 16S rRNA gene sequence in Asashima line differed by over 6% from the standard Nigerian lines (a 3% difference is considered the species threshold in anurans), suggesting that this experimental line is a distinct species from the true X. tropicalis .